1978
DOI: 10.1104/pp.61.6.883
|View full text |Cite
|
Sign up to set email alerts
|

Association between Elemental Content and Fruit Ripening in rin and Normal Tomatoes

Abstract: Analysis of Ca and other inorganic ions in the pericarp of rin, a nonripening mutant, and normal tomato (Lycopersicon esculentum Mill) fruits revealed significant differences in their accumulations at advanced stages of fruit development. During early stages of fruit development, soluble Ca was higher in Rutgers and there were no detectable changes in the accumulation patterns of the other inorganic ions. In the mutant rin, bound Ca continued to increase with age and it was twice as high as compared to earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

1983
1983
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
2
18
1
1
Order By: Relevance
“…Where a simple distinction is made between soluble and bound ions after dispersing the material in water (Suwwan and Poovaiah, 1978;Tieman and Handa, 1994), the data are unreliable because organic acids in the extract may leach cations from the cell wall (Ferguson et al, 1980). Table I1 supports this contention, showing that during the period between 5 and 60 min after tissue disruption losses are occurring from the insoluble material.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Where a simple distinction is made between soluble and bound ions after dispersing the material in water (Suwwan and Poovaiah, 1978;Tieman and Handa, 1994), the data are unreliable because organic acids in the extract may leach cations from the cell wall (Ferguson et al, 1980). Table I1 supports this contention, showing that during the period between 5 and 60 min after tissue disruption losses are occurring from the insoluble material.…”
Section: Discussionsupporting
confidence: 69%
“…Whereas this is the first time an attempt has been made to estimate the level of organic acids in the cell wall space, there have been numerous attempts to measure cell wall calcium. To make a comparison with other methods of estimating cell wall calcium and magnesium, we determined the relative amounts of soluble and bound calcium in aqueous extracts of unripe and ripe fruit (Table 11) following a procedure similar to Suwwan and Poovaiah (1978).…”
Section: Cell Wall-associated Levels Of Organic Acids Calcium and Mmentioning
confidence: 99%
“…Este processo, conforme Suwwan & Poovaiah (1978), pode ter um papel no início do amolecimento dos frutos em amadurecimento.…”
Section: Resultsunclassified
“…Representative samples were finely ground to pass through a 60 mesh screen. The samples were analyzed for soluble and bound 45 Ca by a modified method of Suwaan and Poovaiah (1978 Samples (1.0 ml) from soluble and bound 45 Ca fractions were placed into vials which contained 10 ml of PCS liquid scintillation cocktail (Amersham). Radioactivity was measured with a liquid scintillation counter (LKB Wallac Rackbeta 1215).…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…Incorporation of calcium into the cell wall results in enhanced tissue resistance to PG, although the ecaxt chemical nature of resistance is unresolved (Wills and Tirmazi, 1979; Buescher and Hobson, 1982). Several studies have reported that cell wall bound calcium declines prior to, or simultaneously with the initiation of ripening (Suwaan and Poovaiah, 1978;Rigney and Wills, 1981). Rigney and Wills, (1981) have suggested that mobility of cell wall bound calcium might initiate ripening and precede PG activity which has also been postulated to initiate tomato ripening (No and Tigchelaar, 1977;Tigchelaar et al, 1978;Poovaiah and Nukaya, 1979 Buescher and Tigchelaar, 1975).…”
Section: Introductionmentioning
confidence: 99%